IMPLEMENTASI PENDIDIKAN MULTIKULTURAL DI SMA NEGERI 1 TELUK KERAMAT - Agi Januarti; Amrazi Zakso; Supriadi Supriadi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2019)
This study aims to describe the implementation of multicultural education in 1 Teluk Keramat senior high school. This research is a qualitative research. The research subjects were Principals, Teachers, and Students. The results of the study show the strategies carried out by schools in implementing multicultural education through the implementation of multicultural education in schools seen from the dimension of content integration. integration into self-programmed and programmed self-development activities. Programmed self-development activities in the form of extracurricular activities, and non-programmed self-development activities consist of routine activities carried out on a scheduled basis, spontaneous activities and exemplary activities. Integration into social studies subjects, integration in subjects is carried out in each subject or theme in learning. Supporting factors are the school climate, school curriculum, facilities and infrastructure, the role of teachers, school programs and activities, and students. The inhibiting factors are individual attitudes, lack of diversity media, posters about diversity and multicultural values, and lack of socialization. In addition, multicultural education in the form of practical activities outside of school in particular is still lacking in schools. Efforts to overcome obstacles include emphasizing values of respect, respect and tolerance. Supported by school policies that carry out noble character education, add diversity posters, socialize, conduct activities outside of school by participating students in various activities outside of school.